PENGARUH KONSUMSI MAKAN TERHADAP STATUS GIZI ANAK DI SEKOLAH DASAR - Sani Asri Puspasari (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2017)
The objectives of this research are to know 1) Food comsumption of kid, 2) Nutrionalstatus of kid, 3) The influence of food consumption and nutritional status of kid in Elementary School Muhammadiyah Parakan Temanggung. The type of the research is ex-post facto. The method to collect the data is done by questionnaire as variable of food consumption, documentation to taking data of student and observation as variable of nutritional status of kid. Data analysis techniques descriptive analysis and hypothesis test used product moment correlation begun by prerequisite analysis, that is normality and linearity examination. The results show that food consumption is categorized fair by relative frequency 50,90%, and the nutritional status is fine by relative frequency 40,01%. Based on correlation test, the score of rxy was 0,268. The score of r table in the significant level 5% for total respondents 55 was 0,266 (rxy 0,268> r table 0,266). It means that there was a positive and significant of food consumption and nutritional status of kid. The score of determinant coefficient (R2) was 0,0718, it means that food consumtion and nutritional status gave a positive contribution 7,18% while 92,82% was example education Key word : Food consumption, Nutrional status